Glutamate in plants: metabolism, regulation, and signalling - Forde, B.G.; Lea, P.J.
Glutamate occupies a central position in amino acid metabolism in plants. The acidic amino acid is formed by the action of glutamate synthase, utilizing glutamine and 2-oxoglutarate. However, glutamate is also the substrate for the synthesis of glutamine from ammonia, catalysed by glutamine synthetase. The a-amino group of glutamate may be transferred to other amino acids by the action of a wide range of multispecific aminotransferases. In addition, both the carbon skeleton and a-amino group of glutamate form the basis for the synthesis of g-aminobutyric acid, arginine, and proline. Finally, glutamate may be deaminated by glutamate dehydrogenase to form ammonia and 2-oxoglutarate. The possibility that the cellular concentrations of glutamate within the plant are homeostatically regulated by the combined action of these pathways is examined. Evidence that the wellknown signalling properties of glutamate in animals may also extend to the plant kingdom is reviewed. The existence in plants of glutamate-activated ion channels and their possible relationship to the GLR gene family that is homologous to ionotropic glutamate receptors (iGluRs)in animals are discussed. Glutamate signalling is examined from an evolutionary perspective, and the roles it might play in plants, both in endogenous signalling pathways and in determining the capacity of the root to respond to sources of organic N in the soil, are considered.
Keywords: ENZYMES; GLR GENES; GLUTAMATE; HOMEOSTASIS; IONOTROPIC GLUTAMATE RECEPTORS; METABOLISM; ROOT ARCHITECTURE; SIGNALLING; SYNTHESIS